Regulation of phosphoinositide metabolism in Apicomplexan parasites - Arabiotorre, Angela; Bankaitis, Vytas A.; Grabon, Aby (Frontiers in Cell and Developmental Biology, 2023)
Phosphoinositides are a biologically essential class of phospholipids that contribute to organelle membrane identity, modulate membrane trafficking pathways, and are central components of major signal transduction pathways that operate on the cytosolic face of intracellular membranes in eukaryotes. Apicomplexans (such as Toxoplasma gondii and Plasmodium spp.) are obligate intracellular parasites that are important causative agents of disease in animals and humans. Recent advances in molecular and cell biology of Apicomplexan parasites reveal important roles for phosphoinositide signaling in key aspects of parasitosis. These include invasion of host cells, intracellular survival and replication, egress from host cells, and extracellular motility. As Apicomplexans have adapted the organization of essential signaling pathways to accommodate their complex parasitic lifestyle, these organisms offer experimentally tractable systems for studying evolution, conservation and repurposing of phosphoinositide signaling. In this review, we describe the regulatory mechanisms that control the spatial and temporal regulation of phosphoinositides in the Apicomplexan parasites Plasmodium and T. gondii. We further discuss the similarities and the differences presented by Apicomplexan phosphoinositide signaling relative to how these pathways are regulated in other eukaryotic organisms.